PHYSICAL EDUCATION IN EARLY CHILDHOOD EDUCATION IN A PUBLIC SCHOOL IN MUNICIPAL CANINDÉ / CE: A VISION OF THE INTERN (Fiep Bulletin - online, 2013)
This essay seeks to reflect on the discipline of Supervised Physical Education in Early Childhood Education. The experiment was conducted with 30 children, aged 4-6 years, students from a public school in Canindé - Ceará. It was found that students were initially resistant to new bodily experiences, but that was stopped with practice through the activities taught. The lack of school infrastructure caused several changes in planning teaching, sometimes preventing the practice of activities for everyone. The development of the motor, affective, social and cognitive spheres of the students were accompanied and it was verified beneficial changes. It is considered that the completion of the Supervised practice for undergraduate student in Physical Education provides knowledge acquisition that may not have been acquired in other disciplines of the academic curriculum, providing tools to build a professional identity, approaching him to his reality and future field of work.
Keywords: Early Childhood Education; Stage; Physical Education.